2022
DOI: 10.1253/circj.cj-21-0749
|View full text |Cite
|
Sign up to set email alerts
|

Age-Period-Cohort Analysis of Ischemic Heart Disease Morbidity and Mortality in China, 1990–2019

Abstract: cohort effects, and quantifies the influence of age, time, and birth cohort factors on disease rate. Estimable APC functions provide a useful parametric framework that complements standard non-parametric descriptive methods. 7 Although prior studies in China have applied the APC model to IHD analysis, 8 the data used in these studies was from 1987 to 2013, and the cohorts analyzed were born between 1904 and 1993. The cohort effects in younger generations have not yet been investigated.This study analyzed and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The improvement of the healthcare level has shown to prolong the survival period of patients with heart disease. It can be inferred from the aforementioned results that the incidence and severity of IHD increase with age ( 17 ). Our study also found age differences in the disease burden of IHD in China, and the overall trend of the disease burden of IHD due to controllable risk factors increases with age.…”
Section: Discussionmentioning
confidence: 94%
“…The improvement of the healthcare level has shown to prolong the survival period of patients with heart disease. It can be inferred from the aforementioned results that the incidence and severity of IHD increase with age ( 17 ). Our study also found age differences in the disease burden of IHD in China, and the overall trend of the disease burden of IHD due to controllable risk factors increases with age.…”
Section: Discussionmentioning
confidence: 94%
“…In consistent with previous studies ( 22 , 24 , 28 , 29 ), we found that male patients had higher direct medical costs than female patients. The possible reasons might be the higher IHD burden ( 13 ), higher morbidity of IHD ( 8 ), and more consumption of drinking and smoking ( 66 ) for male patients than female patients, and thus male patients may suffer from more serious cardiovascular disease and incurred higher expenditures.…”
Section: Discussionmentioning
confidence: 99%
“…In China, the incidence of IHD was ~59.1/100,000 in 2012 ( 6 ), and it was predicted that there would be 38.6 million IHD events from 2010 to 2030 ( 7 ). The morbidity and mortality of IHD have been continuously increasing ( 8 ). In 2015, the total mortality of IHD in China was 22,117/100,000, accounting for 1.51 million deaths ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Standardised populations were referenced to the global population of the GBD 2019 data. The specific calculation formula for the statistical indicators is as follows [ 21 ]: where a is the age-specific incidence/DALY rate, b is the age-specific population number, and i is age class.…”
Section: Methodsmentioning
confidence: 99%